Analysis of possible introduction of PV systems considering output power fluctuations and battery technology, employing an optimal power generation mix model. Issue 2 (22nd October 2012) - Komiyama, Ryoichi; Shibata, Saeko; Nakamura, Yosuke; Fujii, Yasumasa
Abstract This paper presents an evaluation of the impact of extensive introduction of photovoltaic (PV) systems and stationary battery technology into the optimal power generation mix in the Kanto and Kinki regions. The introduction of solar PV systems is expected to be extensively deployed in the Japanese household sector and utility companies in order to address the concerns of energy security and climate change. Considering this expected large‐scale deployment of PV systems in electric power systems, it is necessary to investigate the optimal power generation mix which is technologically capable of controlling and accommodating the intermittent output‐power fluctuations inherent in PV systems. Against this background, we develop both a solar photovoltaic power generation model and an optimal power generation mix model, including stationary battery technology, which can be used to explicitly analyze the impact of PV output fluctuations at a detailed time interval resolution such as 10 minutes for 365 consecutive days. Simulation results reveal that PV introduction does not necessarily increase battery technology due to the cost competitiveness of thermal power plants in the load‐following requirement caused by PV systems. Additionally, on the basis of sensitivity analysis on PV system cost, dramatic cost reduction proves to be indispensable for PV to supply bulk electricity similarly to thermal and nuclear power plants. © 2012 Wiley Periodicals, Inc. Electr Eng Jpn, 182(2): 9–19, 2013; Published online in Wiley Online Library (wileyonlinelibrary.com). DOI 10.1002/eej.22329